Analysis of muscle activity during contractions in the three heads of the triceps branchii using surface electromyography
Among all the upper extremity skeletal muscles, the three headed (lateral, long and medial) triceps brachii (TB) is considered as the muscle most responsible for normal and sports activities. In this research, we recorded and evaluated muscle activity among the three heads of TB, using surface electromyography (sEMG) signals, during isometric and isotonic contractions. The commercially available Delsys and PowerLab data acquisition systems were used to record the EMG signals. Isometric contractions were produced by a forceful handgrip task with full elbow extension. 2 different protocols were applied – repetitive isometric contraction and prolonged isometric contraction. 13 participants performed 5 trials, 10 s each, to observe behavior between and within contractions, and 18 participants performed a single trial of 90 s to observe fatiguing effects. On the other hand, isotonic contractions were investigated during a cricket bowling action. 2 different bowling categories were studied – fast bowling (FB) and spin bowling (SB). 10 participants performed 3 overs (1 over = 6 ball deliveries) equivalent to 18 trials for both FB and SB. For the statistical analysis, we computed the mean of the normalized root mean square (RMS) values across all subjects from the collected data. We found muscle activity among the three heads of TB, between repetitive isometric contractions, to be statistically significant (p < 0.05). Muscle activity decreased in the lateral and long heads, but however increased in the medial head. In the case of within contractions, TB muscle strength decreased with increasing contraction duration, and the lowest decrease of muscle strength was observed in the medial head. Results from the prolonged isometric contraction show a gradual decrease in the computed mean of the normalized RMS values across all subjects after a certain time period, indicating the presence of fatigue. Time to fatigue was observed at the lateral, long and medial heads at 50 s, 40 s and 65 s respectively. Fatiguing rates was observed at the long, medial and lateral heads at a slope of -2.863, -2.412 and -1.877 respectively. On the other hand, during the isotonic contractions, we found that the sEMG activities among the three heads of the TB and among the 7 phases of bowling to be statistically significant (p < 0.05). Among the 7 phases, the front-foot contract (FC) phase generated the highest sEMG activity during both FB and SB. We also found that all the heads of the TB were more active in FB than SB. Moreover, the medial head was found to be more active compared to the other heads during all the 7 phases of bowling for both FB and SB. The outcomes of the present research may play a key role in our quest to better understand the physiology and biomechanics of the TB muscle